PRAGMATISME DALAM KANDIDASI CALON ANGGOTA DPR PARTAI NASDEM PADA PEMILU 2019 - Reskianti Windharti; Nurul Nurhandjati (Journal Publicuho, 2021)
This study discusses pragmatism in the process of candidacy for DPR members carried out by a political party, namely the NasDem Party in the 2019 Election. As is known, the NasDem Party is still a new party, but was able to gain a significant increase in votes. Departing from Purbolaksono's research which categorizes the NasDem Party as a catch-all party type, and refers to several expert definitions and previous research on pragmatism, this paper describes how pragmatism occurs in the candidates for legislative members from the NasDem Party. Using the analytical descriptive method, this research begins with a description of how the Nasdem Party's candidacy was carried out, then continued by an analysis accompanied by field facts that support the author's analysis. The findings of this study are that pragmatism in the NasDem Party's candidacy process occurs in 4 (four) forms, namely 1) an open recruitment system that provides opportunities for candidates who change parties before the candidacy process; 2) ideology that is no longer the main thing in the candidacy process; 3) the use of profit and loss logic in the candidacy process; and 4) the existence of a screening process (without going through the Bacaleg program) for legislative candidates who are considered to have the potential to gain votes.